Improvement of the Quality of Landrace Pig Spermatozoa in Diluent of Young Coconut Water and Tris Combination - Ayang C. Tafuli; Thomas Mata Hine; Aloysius Marawali (Jurnal sosial dan sains, 2024)
ABSTRACT Background: The research material used was fresh semen of 2-year-old landrace boars of good quality (spermatozoa motility ≥ 70% and spermatozoa abnormality < 20%) Purpose: This study aimed to find the best combination of young coconut water (YCW) and Tris to improve the quality of landrace boars spermatozoa. Method: %). This study used an experimental method according to a complete randomized design procedure with five treatments and five replicates. The treatments were: T0= YCW, T1= TCW 75% + tris 25%, T2= YCW 50% + tris 50%, T3= YCW 25% + tris 75%, T4= Tris. All treatment diluents were added with 20% egg yolk, 3% moringa leaf extract, 1,000 IU/mL penicillin, and 1,000 µg/mL streptomycin. The variables tested were motility, viability, abnormality, and survival. Results: The observation results at the 40th hour of storage showed that treatment T3 was significantly different (P<0.05) on motility, viability, abnormality and survival but on the variable viability treatment T3 was insignificantly different from T1 (p>0.05), but significantly different from treatment T0, T2, and T4; and for spermatozoa abnormality variables in all treatments were the same (p>0.05) Conclusion: It was concluded that the combination of YCW 75% and tris 25% and 100% tris effectively maintained the quality of landrace boars spermatozoa